A companion to global gender history - Meade, Teresa A. 1948-; Wiesner-Hanks, Merry E. 1952- (Blackwell companions to world history, 2020)
"As a field of scholarly investigation, the history of sexuality is about as old as gender history in its modern, social constructionist form, dating from the 1970s and 1980s. Unlike gender history, whose roots reach back into a variety of disciplines and scholarly fields, the history of sexuality was long regarded as at best a catalogue of anthropological curiosities and at worst a pornographic amusement for social elites. In the 1880s medically informed writers such as Iwan Bloch, Paolo Mantegazza, and Richard von Krafft-Ebing tried to fit the spectrum of human sexual expression into an evolutionary scenario, but the foundations of the field's contemporary respectability were laid in the 1920s by British-trained social anthropologists such as Bronislaw Malinowski and the American Margaret Mead, who studied sexuality in social context and speculated on its relationship to socially ascribed gender roles. Though many of the early medical and anthropological works on sex and society as well as the first academic histories were devoted to the variety of sexual behavior and values in human history, many of their authors were also sex reformers who often used this information as weapons in the long cultural struggle with traditional Western sexual ideology. Gordon Rattray Taylor, whose Story of Society's Changing Attitudes to Sex (1954) was one of the first serious histories of the subject, was unapologetic about his aim of undermining the vestiges of Victorian sexual beliefs. The Western scholars who have studied the historical and global varieties of sexuality are still tempted to look at the subject through a critical and relativizing lens. Historicizing a topic that has been used both as a "natural" universal to command conformity and as a radical tactic of social rebellion has proven difficult indeed"--